Efektivitas Eceng Gondok (Eichhornia crassipes), Hydrilla (Hydrilla verticillata), dan Rumput Payung (Cyperus alterni-folius) dalam Pengolahan Limbah Grey Water - Sy. Ummi Kalsum; A. Napoleon A. Napoleon; Bambang Yudono (Faculty of Mathtmatics and Natural Sciences, 2014)
The purpose of this research is to determine the effectiveness of each phytoremediation agents, namely water hyacinth (Eichhornia crassipes), Hydrilla (Hydrilla verticillata) and Umbrella Grass (Cyperus al-ternifolius) in domestic wastewater remediate greywater manifold. The method used is pupossive sampling. Domestic waste water samples taken from residential waste and plant samples were taken from the field. Do-mestic waste water created within 4 concentrations are 100%, 75%, 5% and 25% and into the each concentra-tion of waste water planted with each phytoremediation agent. The result showed that water hyacinth (Eich-hornia crassipes) with 25% concentration of waste is most effective than the two other phytoremediation agents in remediate waste water with the ability to improve the quality of waste as indicated by the decline in 85% BOD value, 82% COD value, and 86% of TSS value.